Supraorbital eyebrow approach to skull base lesions - Yvens Barbosa Fernandes; Daniel Maitrot; Pierre Kehrli; Oswaldo Ignácio de Tella Jr; Ricardo Ramina; Guilherme Borges (Arquivos de Neuro-Psiquiatria)
We report our experience with a supraorbital eyebrow minicraniotomy. This technique is suitable to lesions situated in the region of the anterior fossa, suprasellar cisterns, parasellar region and Sylvian fissure. A 50 mm incision in the eyebrow and a supraorbital minicraniotomy is performed. Sixteem patients harboring different lesions were operated on with good postoperative and cosmetic results. We conclude that this approach is safe and useful in selected cases.